2023
DOI: 10.1002/mnfr.202300373
|View full text |Cite
|
Sign up to set email alerts
|

Dityrosine Aggravates Hepatic Insulin Resistance in Obese Mice by Altering Gut Microbiota and the LPS/TLR4/NF‐κB Inflammatory Pathway

Yin‐Yi Ding,
Jinchi Lan,
Yumeng Fang
et al.

Abstract: ScopeDityrosine is the main product of protein oxidation, which has been proved to be a threat to human health. This study aims to investigate whether dityrosine exacerbates insulin resistance by inducing gut flora disturbance and associated inflammatory responses.Methods and resultsMice fed with normal diet or high‐fat diet (HFD) received daily gavage of dityrosine (320 µg kg−1 BW) or saline for consecutive 13 weeks. The effects of dityrosine on gut microbiota are verified by in vitro fermentation using fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, after oral administration of MFT extract to GK rats, there was a significant reduction in the height of the duodenal villi. This LPS is a biomolecule that can trigger the body's inflammatory response, and its role is to release inflammatory mediators, ultimately leading to insulin resistance [45]. We measured the levels of the pro-inflammatory substance LPS and the inflammatory mediator Il-1β in the serum.…”
Section: Effects Of Mft Extract On Duodenal and Kidney Morphology In ...mentioning
confidence: 99%
“…However, after oral administration of MFT extract to GK rats, there was a significant reduction in the height of the duodenal villi. This LPS is a biomolecule that can trigger the body's inflammatory response, and its role is to release inflammatory mediators, ultimately leading to insulin resistance [45]. We measured the levels of the pro-inflammatory substance LPS and the inflammatory mediator Il-1β in the serum.…”
Section: Effects Of Mft Extract On Duodenal and Kidney Morphology In ...mentioning
confidence: 99%
“…It has been established that food-derived Dityr may be linked to the development of chronic noncommunicable health threats, including energy metabolism disorders, hepatic steatosis, and brain damage. Mechanistic studies have confirmed that oxidative stress may be one of the key factors in Dityr-induced health issues, leading to mitochondrial function damage. Given these findings, investigating the relationship between Dityr and oxidative stress is currently a highly relevant research topic. Recent studies on inflammation mechanisms have also confirmed that oxidative stress not only directly induces damage to cellular components, such as lipids, proteins, and nucleic acids, but also acts as an inducer of inflammation …”
Section: Introductionmentioning
confidence: 96%
“…After highly oxidized food enters the gastrointestinal tract, a large amount of free Dityr is released from the peptide chain and absorbed by the gastrointestinal tract by the action of the digestive system . It has been established that food-derived Dityr may be linked to the development of chronic noncommunicable health threats, including energy metabolism disorders, hepatic steatosis, and brain damage. Mechanistic studies have confirmed that oxidative stress may be one of the key factors in Dityr-induced health issues, leading to mitochondrial function damage. Given these findings, investigating the relationship between Dityr and oxidative stress is currently a highly relevant research topic.…”
Section: Introductionmentioning
confidence: 99%